Lenticulostriate Vasculopathy in Brain Ultrasonography is Associated with Cytomegalovirus Infection in Newborns - Syuan-Yu Hong; Jiann-Jou Yang; Shuan-Yow Li; Inn-Chi Lee (Elsevier, 2015)
Lenticulostriate vasculopathy is associated with various disorders, in particular cytomegalovirus infection, which can cause neurological consequences. We wanted to evaluate the association of lenticulostriate vasculopathy and cytomegalovirus infection. We retrospectively collected data on lenticulostriate vasculopathy from 858 neonatal ultrasonography scans. Methods: Fifty-five patients with lenticulostriate vasculopathy were diagnosed. Lenticulostriate vasculopathy was classified as severe and mild according to the ultrasonographic findings. We analyzed gender, unilateral and bilateral lenticulostriate vasculopathy, mild and severe lenticulostriate vasculopathy, intrauterine growth retardation, and lenticulostriate vasculopathy associated with other brain malformations to determine whether they were correlated with cytomegalovirus infection. Results: Neonatal cytomegalovirus infections correlated primarily with lenticulostriate vasculopathy that was associated with brain structure anomalies p < 0.0001, followed by severe lenticulostriate vasculopathy (p = 0.029). Cytomegalovirus urine polymerase chain reaction ratios were 69% for severe and 23% for mild lenticulostriate vasculopathy (p = 0.002; odds ratio = 7.33). Of 72 newborns with intrauterine growth retardation without lenticulostriate vasculopathy, 33 were analyzed for cytomegalovirus, of whom only one was positive, which was significantly different from the newborns with lenticulostriate vasculopathy (p = 0.003; odds ratio = 11.64). Conclusion: Lenticulostriate vasculopathy on neonatal ultrasonography is useful for predicting cytomegalovirus infection, particularly in severe lenticulostriate vasculopathy. When severe lenticulostriate vasculopathy is associated with a brain structure anomaly, cytomegalovirus infection should be considered. The outcomes for the cases in which cytomegalovirus infection was associated with other brain structure anomalies were significantly worse than the outcomes in cases associated with lenticulostriate vasculopathy only.